Pendampingan Kurasi Mandiri Bacaan Sastra Siswa bagi Guru Mata Pelajaran Bahasa Indonesia di SMP Wachid Hasyim Kota Malang - Ambarwati, Ari; Muttaqin, Khoirul; Tabrani , Ahmad (Sasambo: Jurnal Abdimas (Journal of Community Service), 2025)
Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi guru Bahasa Indonesia di SMP Wachid Hasyim Kota Malang dalam melakukan kurasi bacaan sastra siswa. Berdasarkan analisis situasi, sebagian besar guru belum memahami kebijakan sastra dalam kurikulum dan kesulitan memilih bahan bacaan sesuai karakteristik siswa. Kegiatan diikuti oleh empat guru dengan tahapan pre-test, pendampingan, dan post-test. Hasil menunjukkan peningkatan rata-rata skor pemahaman dari 68 menjadi 86. Guru menunjukkan peningkatan kemampuan dalam memilih bacaan yang relevan dan menyusun RPP yang lebih kreatif dan kontekstual. Kegiatan ini membuktikan efektivitas pendampingan kurasi bacaan dalam memperkuat literasi sastra dan mendukung SDG 4 (Pendidikan Berkualitas).Literary Reading Curation Assistance for Indonesian Language Teachers at Wachid Hasyim Junior High School, Malang CityThis community service activity aims to improve the competence of Indonesian language teachers at Wachid Hasyim Junior High School, Malang City in curating students' literary readings. Based on the analysis of the situation, most teachers do not understand the literary policy in the curriculum and have difficulty choosing reading materials according to the characteristics of students. The activity was attended by four teachers with pre-test, mentoring, and post-test stages. The results showed an increase in the average comprehension score from 68 to 86. Teachers show improved ability to choose relevant readings and prepare more creative and contextual lesson plans. This activity proves the effectiveness of reading curation assistance in strengthening literary literacy and supporting SDG 4 (Quality Education).Literary Reading Curation Assistance for Indonesian Language Teachers at Wachid Hasyim Junior High School, Malang CityThis community service activity aims to improve the competence of Indonesian language teachers at Wachid Hasyim Junior High School, Malang City in curating students' literary readings. Based on the analysis of the situation, most teachers do not understand the literary policy in the curriculum and have difficulty choosing reading materials according to the characteristics of students. The activity was attended by four teachers with pre-test, mentoring, and post-test stages. The results showed an increase in the average comprehension score from 68 to 86. Teachers show improved ability to choose relevant readings and prepare more creative and contextual lesson plans. This activity proves the effectiveness of reading curation assistance in strengthening literary literacy and supporting SDG 4 (Quality Education).